Persepsi Ibu, Dukungan Suami dan Dukungan Tempat Kerja dengan Pemberian Asi Ekslusif pada Ibu Bekerja di CV X - Erika Srirahayu Ningsih; Retno Sugesti; Milka Anggreni Karubuy (MPI Press, 2021)
Introduction: Failure, The success of exclusive breastfeeding is due to the working mother .The failure factor to exclusively offer breastfeeding to working mothers is due to working mothers and the unavailability of breastfeeding room facilities and lack of support from the workplace. Objectives: The research objective was to determine the mother's perception, husband's support and workplace support by giving exclusive breastfeeding to working mothers at CV. Tri Corp Bogor Regency in 2019. Method: The research design used was a cross sectional study. The population in this study were mothers who worked at CV. Tri Corp Bogor Regency as many as 42 people. The sample used was 43 respondents with the sampling technique with the total sampling method. Data analysis using Chi Square test. Result: Based on the results of the investigation, it was found that 22 people were given exclusive breastfeeding (53.4%), 22 people had poor perceptions of mothers (53.4%), 23 people (54.8%) had poor support, local support good work as many as 24 people (57.1%). The statistical test results of the relationship between maternal perceptions and exclusive breastfeeding with a P value = 0.014. The relationship between partner support and exclusive breastfeeding with a P value = 0.032. The relationship between workplace support of exclusive breastfeeding with a P value = 0.011. Conclution: The conclusion is that there is a relationship between maternal perceptions, workplace support and support by providing exclusive breastfeeding for mothers working at CV. Tri Corp Bogor Regency in 2019. Suggestions for research sites to be able to provide health workers for pregnant and breastfeeding mothers as well as increase breastfeeding space and provide exclusive breastfeeding policies for mothers with children 0-6 months.